Amelioration of Coal Post Mining Area In Promoting The Growth of Avocado (Persea Americana Mill.) - Gindo Tampubolon; Itang Ahmad Mahbub; Neliyati Neliyati (Jurnal Silva Tropika, 2019)
This study was aimed to obtain the composition of ameliorant that gives the best result in recovering several chemical properties of coal post mining area in reclamation as well as in promoting the growth of avocado in the area. The study was carried out in post mining area of PT Nan Riang from April to October 2017 using Experimental Method with Randomized Group Design consisting of 5 treatments with different composition of ameliorant, a1 = 1 kg composted chicken manure + limestone (0,50 x Al-dd) + 25 g biochar /plant, a2 = 2 kg composted chicken manure + limestone (1,00 x Al-dd) + 50 g biochar /plant, a3 = 3 kg composted chicken manure + limestone (1,25 x Al-dd) + 75 g biochar /plant, a4 = 4 kg composted chicken manure + limestone (1,50 x Al-dd) + 100 g biochar /plant dan a5 = 5 kg composted chicken manure + limestone (1,75 x Al-dd) + 125 g biochar /plant. The results showed that the treatment by ameliorant composition had real influence on the increase of the plant’s height, unreal influence on the increase of the plant’s diameter, real influence on the soil pH, and unreal influence on the soil organic-C content and cation-exchange capacity. Also, it can be seen from the DMRT 5% test that the best composition of ameliorant in promoting the plant’s height was at 4 kg composted chicken manure+ limestone (1,50 x Al-dd) + 100 g biochar /plant, while that in improving the soil pH was at 5 kg composted chicken manure + limestone (1,75 x Al-dd) + 125 g biochar /plant.